The Flipped Classroom Effect on Students’ Self-Regulated Learning - Selvia Erita; Egha Ardhia Pramesty; Aan Putra (Edumatika : Jurnal Riset Pendidikan Matematika, 2022)
The Covid-19 pandemic has had a significant impact on the education system around the world, leading to changes in the implementation of learning that reduce the number of face-to-face meetings and require students to engage in more self-regulated learning. To ensure optimal student learning achievement despite studying independently, teachers must select a suitable model. One alternative solution to increase self-regulated learning is the Flipped Classroom model. Therefore, this study aims to examine the effectiveness of the Flipped Classroom model in promoting students' self-regulated learning. To investigate the effectiveness of the Flipped Classroom model, a quasi-experimental research design was employed, using a pretest-posttest nonequivalent control group design at a State Islamic Junior High School in Kerinci, Jambi. Data was collected through a self-regulated learning questionnaire, and the hypothesis was tested using a t-test. The results of the study indicate that the Flipped Classroom model is highly effective in increasing students' self-regulated learning in mathematics. As such, this model is highly suitable for sustainable application at all levels of education in the future.